(untitled) (Proceedings of the International Conference on Education, 2025)
Modern educational theories have emphasized that the student is the focus of the educational process, and the faculty member is a guide and mentor. Given the importance of educational specializations in graduating competent teachers to work in the educational field, this study came to present a model of teaching excellence based on the student lecturer in educational specializations and the opinions of university students towards it. This model focuses on enabling the student in higher education to possess teaching competencies. The researcher used the qualitative approach through standardized interviews and the quasi-experimental approach by proposing a teaching model based on the student lecturer. The study consisted of 37 students registered in teaching methods and theoretical training for the Bachelor’s program in vocational education for the second semester of the academic year 2023/2024. They were assigned to teach the course topics and interviews were conducted with them after the end of teaching to find out their opinions towards the teaching model. The study results showed that the proposed teaching model consisted of six stages: analysis, planning, preparation and design, preparation and equipment, implementation, follow-up and evaluation. The students’ opinions about the proposed model were positive and encouraged its use in various courses. One of the students said, “When a student explains the subject to others, he achieves a set of benefits: he learns more and enhances his understanding. He develops the student’s communication skills when he explains the concepts simply and clearly. The student feels confident and proud when he can help his colleagues understand. The student learns leadership and cooperation skills when he assumes the role of the teacher. The student becoming the teacher benefits everyone. It improves the student’s performance and encourages them. It improves the student’s personality. It gives the student the skill and experience to become a successful teacher in the future. The student provides himself with feedback by writing the presentation and explaining it to the students. It improves student interaction by using educational tools and presentations.” The researcher explains those interested in the higher education sector in applying the teaching model of improvement on a wider scale in educational programs.